Sex‐gender disparities in nonagenarians with acute coronary syndrome. Issue 3 (19th January 2021) - Cepas‐Guillen, Pedro L.; Echarte‐Morales, Julio; Flores‐Umanzor, Eduardo; Fernandez‐Valledor, Andrea; Caldentey, Guillem; Viana‐Tejedor, Ana; Martinez Gomez, Eduardo; Tundidor‐Sanz, Elena; Borrego‐Rodriguez, Javier; Vidal, Pablo; Llagostera, Marc; Quiroga, Xavier; et al.
Abstract: Background: Acute coronary syndrome (ACS) remains one of the leading causes of mortality for women, increasing with age. There is an unmet need regarding this condition in a fast‐growing and predominantly female population, such as nonagenarians. Hypothesis: Our aim is to compare sex‐based differences in ACS management and long‐term clinical outcomes between women and men in a cohort of nonagenarians. Methods: We included consecutive nonagenarian patients with ACS admitted at four academic centers between 2005 and 2018. The study was approved by the Ethics Committee of each center. Results: A total of 680 nonagenarians were included (59% females). Of them, 373 (55%) patients presented with non‐ST‐segment elevation ACS and 307 (45%) with ST‐segment elevation myocardial infarction (STEMI). Men presented a higher disease burden compared to women. Conversely, women were frailer with higher disability and severe cognitive impairment. In the STEMI group, women were less likely than men to undergo percutaneous coronary intervention (PCI) (60% vs. 45%; p = .01). Overall mortality rates were similar in both groups but PCI survival benefit at 1‐year was greater in women compared to their male counterparts (82% vs. 68%; p = .008), persisting after sensitivity analyses using propensity‐score matching (80% vs. 64%; p = .03). Conclusion: Sex‐gender disparities have been observed in nonagenarians. Despite receiving less often invasive approaches, women showed better clinical outcomes. Our finding may help increase awareness and reduce the current gender gap in ACS management at any age.